Artificial Intelligence Technology - Huawei Technologies Co., Ltd (Springer Nature, 2023)
This open access book aims to give our readers a basic outline of today's research and technology developments on artificial intelligence (AI), help them to have a general understanding of this trend, and familiarize them with the current research hotspots, as well as part of the fundamental and common theories and methodologies that are widely accepted in AI research and application. This book is written in comprehensible and plain language, featuring clearly explained theories and concepts and extensive analysis and examples. Some of the traditional findings are skipped in narration on the premise of a relatively comprehensive introduction to the evolution of artificial intelligence technology. The book provides a detailed elaboration of the basic concepts of AI, machine learning, as well as other relevant topics, including deep learning, deep learning framework, Huawei MindSpore AI development framework, Huawei Atlas computing platform, Huawei AI open platform for smart terminals, and Huawei CLOUD Enterprise Intelligence application platform. As the world's leading provider of ICT (information and communication technology) infrastructure and smart terminals, Huawei's products range from digital data communication, cyber security, wireless technology, data storage, cloud computing, and smart computing to artificial intelligence.